Rohingya Genocide in the Perspective of International Criminal Law and Global Responsibility - Sulvy Mandriyani (Scholar Center, 2024)
The ethnic diversity in Myanmar is also a cause of conflict between different ethnic groups, especially between the majority and minority ethnic groups in this country. One of the most famous ethnic conflicts and in the world spotlight is the Rohingya ethnic conflict. This type of research is normative legal research. The procedure for collecting legal documents is carried out through literature studies. The nature of the research used in this study uses prescriptive-normative research. The results of the study indicate that there have been crimes against humanity against the Rohingya ethnic group in western Myanmar in the form of slavery, deportation or forced repatriation, sexual violence, and torture so that it can be stated that crimes against humanity against the Rohingya in western Burma are international crimes and are worthy of being called a case of genocide. The actions taken by the Myanmar government are violations of human rights in the Rohingya case, including the crime of genocide and also crimes against humanity. then the non-recognition of the Rohingya ethnic group into the list of ethnic groups in Myanmar is an attempt to eliminate existing ethnic groups.